2018
DOI: 10.1039/c8cp05330h
|View full text |Cite
|
Sign up to set email alerts
|

Operando investigations of lithiation and delithiation processes in a BiVO4 anode material

Abstract: Conversion and alloying reactions in BiVO4 as an anode material for lithium-ion batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 25 publications
(24 reference statements)
4
14
0
Order By: Relevance
“…8,20 Both area-summed data (increasing maximum r in the PDFs and appearance of Bragg peaks in conventional XRD) and maps from TSCT show that crystallite size increases with cycling. This has been observed in other bismuth metallate anodes (in both LIBs and NIBs) 12,19,21 , as well as for other conversion/alloying anode materials e.g. bismuth sulphide 22 .…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…8,20 Both area-summed data (increasing maximum r in the PDFs and appearance of Bragg peaks in conventional XRD) and maps from TSCT show that crystallite size increases with cycling. This has been observed in other bismuth metallate anodes (in both LIBs and NIBs) 12,19,21 , as well as for other conversion/alloying anode materials e.g. bismuth sulphide 22 .…”
Section: Discussionsupporting
confidence: 63%
“…Coin cell tests at a cycling rate of C/6.6 on the BiVO4/super P carbon/PAA binder composition used for the operando experiments showed that it performs as expected from our earlier studies. 12 The cells showed stable retained capacity of around 350 mAh g -1 between 250 and 500 cycles (supporting fig. S3).…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…The use of structures from density functional theory (DFT) calculations (energy minimisations both of known structures from databases and invented structures produced, e. g. by replacement of certain atom types in a known structure) has already proved important in interpreting operando data from NIBs [42,43,171,206,218,224–226] . We expect such methods to find new applications as operando experiments develop further and come into wider use.…”
Section: Methods For Analysis Of Operando Data and New Experimental Methodologiesmentioning
confidence: 99%